Immersive Audio Signal Processing - Bharitkar, Sunil; Kyriakakis, Chris (Information Technology: Transmission, Processing and Storage, 2006)
This text introduces graduate students and researchers to the basics of digital signal processing relevant to audio/acoustics and psychoacoustics and a variety of topics and latest results in immersive audio processing research. Kay features: Covers relevant background material adequately Topics include immersive audio synthesis and rendering, multichannel room equalization, audio selective signal cancellation, signal processing for audio applications, surround sound processing, psychoacoustics and its incorporation in audio signal processing algorithms for solving various problems Real-world measurements depicted in the book demonstrate efficiency and power of the various solutions presented This timely graduate textbook targets courses on Immersive Audio Signal Processing, DSP and Multimedia Processing, and is an invaluable reference for researchers interested in understanding the synergy between acoustics/audio signal processing and psychoacoustics, and how these are melded to solve various hot topics in immersive multichannel audio processing.